PENERAPAN MODEL PORTFOLIO BASED LEARNING UNTUK MENINGKATKAN CIVIC SKILLS SISWA PADA PEMBELAJARAN PKn di SEKOLAH DASAR - Widya Trio Pangestu , Prima Rias Wana (Universitas PGRI Yogyakarta, 2017)
The purpose of this research is to improve the students' active participation and citizenship skills (civic skills) students learning civics in elementary schools using themodel of Portfolio Based Learning. Skills citizenship (civic skills) is a component that isvery important to have students as the embodiment of good citizens (good citizen). Thisstudy uses a qualitative approach, whereas this kind of research is action research (ActionResearch). The collection of data through observation, interviews, and documentation andanalyzed by reflecting on the observation during the action (action). The results showed thatthe use of portfolio models based learning in teaching civics can increase activeparticipation and citizenship skills (civic skills) students in the learning process. It is seenfrom the value of the activity and citizenship skills of students has increased from the firstcycle to the second cycle are already shown on the percentage of success of the studentactivity by 67.00% to 81.00% in the second cycle. While the citizenship skills of studentsfrom 53.44% in the first cycle increased to 77.81% or with a very good category (A) in thesecond cycle.Keywords: a model portfolio based learning, civic skills, Civics EducationÂ